Pengaruh Harga Pupuk, Harga CPO Dan Harga Jual TBS Terhadap Kesejahteraan Petani Sawit Di Kecamatan Pematang Bandar Kabupaten Simalungun Di Tinjau Dari Perspektif Ekonomi Islam - Egi Regi Prayoga; Sri Sudiarti; Khairina Tambunan (Lembaga Pengembangan Kinerja Dosen, 2023)
This research discusses the influence of fertilizer prices, CPO prices, FFB selling prices on the welfare of palm oil farmers from an Islamic economic perspective. This research aims to determine the influence of fertilizer prices, CPO prices, FFB selling prices on the welfare of palm oil farmers from an Islamic economic perspective. This research data is primary data obtained directly from the first source, both from individuals and individuals, such as the results of filling out questionnaires and observations. The data analysis technique used is multiple linear regression analysis using SPSS (Statistical Package For Social Science) 23 software. The results of the research conducted show that fertilizer prices have a positive and significant effect on the welfare of oil palm farmers in Pematang Bandar District, Simalungun Regency. CPO prices have a positive and significant effect on the welfare of oil palm farmers in Pematang Bandar District, Simalungun Regency. The selling price of FFB has a positive and significant effect on the welfare of oil palm farmers in Pematang Bandar District, Simalungun Regency.